Tayma, Saudi-Arabien. Survey im Gräberfeld von Rujum Saʿsaʿ - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2017)
A first systematic surface survey has been carried out in Rujum Saʿsaʿ, an ancient burial ground located south of the oasis of Tayma, increasingly threatened by infrastructural projects of the modern settlement. Within a 700 × 100 m large transect altogether 109 units, 101 of which are graves, were identified and recorded by Structure from Motion. There are three main types of structures: circular graves built of at least two rings of different height resulting in a stepped section; circular graves with cross-shaped interior; and rectangular graves attached to each other at the long side. The associated materials contained human bones, artifacts (primarily beads) and pottery. The latter is dominated by sherds covering most of the 2nd millennium BC. Less represented is Iron Age material (11th to 5th centuries BC). Only few sherds can be dated to the 3rd millennium BC.